Thermo-flow characteristics of indirect dry cooling system with elliptically arranged heat exchanger bundles around a traditional circular cooling tower. (5th July 2017) - Chen, Lin; Liao, Hai-Tao; Huang, Xian-Wei; Yang, Li-Jun; Du, Xiao-Ze; Yang, Yong-Ping
Highlights: Full scale models of indirect dry cooling system are developed. Elliptically arranged heat exchanger surrounds traditional cooling tower. Thermo-flow performance in the absence and presence of wind are investigated. Heat exchanger in elliptical arrangement fits regions with strong prevailing wind. Abstract: In a traditional indirect dry cooling system, the heat exchanger bundles are circularly arranged around the circumference of a cooling tower, which suffers severely from ambient winds. In this paper, an elliptical arrangement of heat exchanger bundles, which surround a traditional circular cooling tower, is proposed to restrain the adverse impacts of ambient winds. Elliptically arranged heat exchanger bundles with four different minor to major axis ratios were investigated on the condition that the total heat transfer area is the same as the traditional indirect dry cooling system. The flow and temperature fields of cooling air in the absence/presence of ambient winds were obtained. The mass flow rate, heat rejection and outlet water temperature of the alternative indirect dry cooling systems were calculated and analyzed. The results show that the elliptically arranged heat exchanger with a small ratio of minor to major axis is superior in thermo-flow performance at high wind speed. It is recommended that indirect dry cooling system incorporating elliptically arranged heat exchanger bundles be applied in regions with strong prevailing winds to achieve better thermo-flow performance.